Frequency, phenotypes, and neuroimaging of early post stroke movement disorders: a prospective study - Eslam Samra; Tamer Roushdy; Amr S. Zaki; Alia H. Mansour; Ahmed Elbassiouny; Ali Shalash (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background A prospective observational study recruited patients with acute stroke. Patients were assessed for the presence of post-stroke movement disorders PSMDs during the first week of stroke. This study aimed to identify the frequency, clinical characteristics, and neuroimaging of early PSMDs (within the first week) and followed for 1 year. Results A total of 600 patients were recruited; 21 patients (3.5%) with PSMDs were detected. Thirteen (2.2%) patients presented with intention tremor/ataxia and eight (1.3%) presented with other movement disorders (most commonly, chorea and tremor). One patient presented with periodic left upper limb shaking with right subcortical watershed infarction, and one patient developed palatal myoclonus with right middle cerebral artery infarction. Patients with PSMDs had significantly lower stroke severity (NIHSS) and were more likely to have lacunar strokes (p < 0.001 and < 0.006, respectively) than patients without PSMDs. Early PSMDs were more associated with posterior circulation strokes (84.25%). Conclusions Early PSMDs are commonly hyperkinetic, more associated with small vessel disease, and less severe and posterior circulation strokes, implying their clinical importance for the proper management of stroke patients.